Composite solid electrolyte membrane and preparation method and application thereof

By using polyvinylidene fluoride-hexafluoropropylene, oxide powder, lithium salt and 3-triethoxysilyl ethyl propionate in the composite solid electrolyte membrane, the discoloration and gelation problems caused by alkaline substances during the preparation process are solved, and a high-performance composite solid electrolyte membrane is achieved.

CN119581644APending Publication Date: 2025-03-07GUANGDONG DIANWANG GONGSI YUNFU POWER SUPPLY BUREAU +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411822618.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Discoloration and gelation problems caused by alkaline substances during the preparation process of existing composite solid electrolytes affect the quality and performance of the film.

Method used

A composite solid electrolyte membrane including polyvinylidene fluoride-hexafluoropropylene, oxide powder, lithium salt and 3-triethoxysilyl ethyl propionate is used to remove residual alkali on the surface of the oxide electrolyte filler by reasonably combining components to improve the fluidity of the slurry and film formation uniformity.

Benefits of technology

It significantly improves the discoloration and gelation problems during the preparation of composite electrolytes, improves the ionic conductivity and mechanical properties of the film, and is suitable for industrial-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a composite solid electrolyte membrane as well as a preparation method and application thereof. The composite solid electrolyte membrane comprises the following components: polyvinylidene fluoride-hexafluoropropylene, oxide powder, lithium salt and ethyl 3-triethoxy silane propionate. Through reasonable compatibility of the components, the coating uniformity is high, the problems of discoloration and gelation in the preparation process of the composite electrolyte can be obviously improved, and meanwhile, the composite electrolyte has relatively low impedance, relatively high ionic conductivity and excellent performance, and has relatively great application potential in preparation of a solid-state battery. In addition, according to the preparation method of the composite solid electrolyte membrane, repeated washing and long-time treatment are not needed, the process is simple and environmentally friendly, the production time and energy consumption are reduced, and the preparation method is suitable for industrial large-scale application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrolyte technology, and in particular to a composite solid electrolyte membrane and a preparation method and application thereof. Background Art

[0002] Existing liquid electrolyte lithium-ion batteries will be difficult to meet the needs of the rapidly developing electric vehicle market in terms of safety and energy density. Using solid electrolytes instead of liquid electrolytes can improve battery safety and energy density by about 66%, so solid-state batteries have become the focus of next-generation battery technology.

[0003] There are many types of solid electrolyte systems. Inorganic solid electrolytes have high ionic conductivity and good thermal stability, but they are hard, have poor interface contact, and are expensive. Organic solid electrolytes have good flexibility, good interface contact, and are low in cost, but have low room temperature ionic conductivity. Organic / inorganic composite system can combine the advantages of both, but in the preparation process of PVDF-HFP (polyvinylidene fluoride-hexafluoropropylene) or PVD (physical vapor deposition) / oxide composite solid electrolyte, PVDF-HFP will undergo HF (hydrogen fluoride) reaction due to the weak alkaline environment of the oxide, generating dark gel, resulting in decreased membrane quality. This is because the oxide electrolyte uses excessive lithium hydroxide or lithium carbonate as a lithium source, and a small amount of alkaline substances remain in the generated powder, and it is not very stable in the air. The lithium ions in it are easy to exchange protons with water in the air to generate alkaline substances such as lithium hydroxide; this weak alkaline environment will trigger the HF removal reaction of PVDF-HFP, and the generated carbon-carbon unsaturated double bonds will cross-link and reduce the fluidity of the slurry and even produce gel, resulting in the inability to evenly mix the oxide electrolyte components, thereby affecting the ion transport and mechanical properties of the composite solid electrolyte, and affecting the coating and film formation of the slurry, which is not conducive to large-scale production. In addition, the formation of carbon-carbon unsaturated double bonds also reduces the flexibility of the molecular chain, thereby increasing the interface resistance of PVDF-HFP and oxide electrolyte fillers. Summary of the invention

[0004] Based on this, it is necessary to provide a composite solid electrolyte membrane and a preparation method and application thereof, which can significantly improve the discoloration and gelation problems of the composite solid electrolyte slurry during the preparation process.

[0005] The technical solution of this application is as follows:

[0006] In a first aspect of the present invention, a composite solid electrolyte membrane is provided, which comprises the following components:

[0007] Polyvinylidene fluoride-hexafluoropropylene, oxide powder, lithium salt and ethyl 3-triethoxysilyl propionate.

[0008] In one embodiment, the lithium salt includes one or more of lithium cyanide, LiN(CN)2, Li(CF3SO2)3C, LiC4F9SO3, LiN(SO2CF2CF3)2, LiB(C2O4)2, lithium bis(oxalate)borate, LiBF4, LiBF3(C2F5), lithium difluoro(oxalate)borate, lithium oxalatedifluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, LiAsF6, LiSbF6 and LiClO4.

[0009] In one embodiment, the oxide powder includes one or more of lithium lanthanum zirconium oxide powder, lithium aluminum titanium phosphate powder, lithium aluminum germanium phosphate powder and lithium lanthanum titanate powder.

[0010] In one of the embodiments, the mass ratio of 3-triethoxysilylethyl propionate to oxide powder is 1:(0.2~1.5).

[0011] In one of the embodiments, the mass ratio of the oxide powder to polyvinylidene fluoride-hexafluoropropylene is (0.05~0.6):1.

[0012] In one of the embodiments, the mass ratio of the polyvinylidene fluoride-hexafluoropropylene and the lithium salt is (1~20):1.

[0013] A second aspect of the present invention provides a method for preparing the composite solid electrolyte membrane as described above, comprising the following steps:

[0014] The oxide powder, ethyl 3-triethoxysilyl propionate and a solvent are mixed to prepare a mixed solution;

[0015] The polyvinylidene fluoride-hexafluoropropylene and lithium salt are added to the mixed solution, stirred, and dried to obtain the product.

[0016] In one embodiment, the step of preparing the mixed solution comprises: directly mixing and stirring the oxide powder, ethyl 3-triethoxysilyl propionate and a solvent; and / or

[0017] First, the ethyl 3-triethoxysilyl propionate and the solvent are mixed and stirred, and then the oxide powder is added.

[0018] A third aspect of the present invention provides a solid-state battery comprising the composite solid-state electrolyte membrane as described above.

[0019] A fourth aspect of the present invention provides an electrical device comprising the solid-state battery as described above.

[0020] Compared with the prior art, this application has the following beneficial effects:

[0021] This application aims at the discoloration and gelation problems caused by alkaline substances in the preparation process of composite solid electrolytes. After rationally designing the components of the composite solid electrolyte membrane, a composite solid electrolyte membrane including polyvinylidene fluoride-hexafluoropropylene, oxide powder, lithium salt and 3-triethoxysilyl ethyl propionate is obtained. After the components are rationally matched, the coating uniformity is high, which can significantly improve the discoloration and gelation problems in the preparation process of the composite electrolyte. At the same time, it has low impedance and high ionic conductivity, excellent performance, and has great application potential in the preparation of solid-state batteries.

[0022] In addition, the preparation method of the composite solid electrolyte membrane of the present application does not require repeated washing and long-term treatment, the process is simple and environmentally friendly, reduces production time and energy consumption, and is suitable for industrial-scale applications.

[0023] The principle of using ethyl 3-triethoxysilyl propionate to remove residual alkali on the surface of oxide electrolyte filler is as follows:

[0024] 3-Triethoxysilyl ethyl propionate is used to remove the residual alkali on the surface of the oxide electrolyte filler. The ester group on the polymer additive will undergo an ester decomposition reaction with the residual alkali on the surface of the oxide electrolyte filler to generate ethanol and triethoxysilyl lithium propionate. Ethanol evaporates when drying, and triethoxysilyl lithium propionate acts as a protective layer for the inorganic solid electrolyte, thereby avoiding the influence of residual alkali on the PVDF-HFP-based polymer, reducing the fluidity of the slurry, and preventing uneven film formation of the electrolyte membrane. The oxygen atoms on the triethoxysilyl lithium propionate will coordinate with lithium ions to enhance the boundary effect of the composite solid electrolyte. At the same time, the triethoxysilyl group and the PVDF-HFP-based polymer have high solubility, which indirectly improves the compatibility between the oxide electrolyte filler and the PVDF-HFP matrix, ensuring the uniform distribution of the oxide electrolyte filler in the composite solid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0026] Figure 1 This is a color test result diagram before adding the polymer additive in Comparative Example 1.

[0027] Figure 2 This is a color test result diagram after adding the polymer additive in Example 1.

[0028] Figure 3It is a graph of impedance test results (Nyquist graph) of Example 1 and Comparative Example 1, where the abscissa is the real part of the impedance and the ordinate is the negative number of the imaginary part of the impedance. DETAILED DESCRIPTION

[0029] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0031] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0032] As used herein, "one or more" refers to any one, any two, or any two or more of the listed items.

[0033] Herein, the optional scope of "and / or", "or / and", and "and / or" includes any one of two or more relevant listed items, and also includes any and all combinations of the relevant listed items, wherein said any and all combinations include any two relevant listed items, any more relevant listed items, or a combination of all relevant listed items. (It should be noted that when at least three items are connected by at least two conjunctions selected from "and / or", "or / and", and "and / or", it should be understood that in the present application, the technical solution undoubtedly includes technical solutions that are all connected by "logical AND", and also undoubtedly includes technical solutions that are all connected by "logical OR". For example, "A and / or B" includes three parallel solutions of A, B and A+B. For another example, the technical solution of "A, and / or, B, and / or, C, and / or, D" includes any one of A, B, C, and D (that is, technical solutions that are all connected by "logical OR"), and also includes any and all combinations of A, B, C, and D, that is, a combination of any two or any three of A, B, C, and D, and also includes a combination of four items of A, B, C, and D (that is, a technical solution that is all connected by "logical AND").)

[0034] Herein, "further", "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of this application.

[0035] Herein, "first aspect", "second aspect", "third aspect", "fourth aspect", etc. are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. In addition, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of the present application, the meaning of "several" is at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0036] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0037] Only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an undefined range; and any lower limit can be combined with other lower limits to form an undefined range, and any upper limit can be combined with any other upper limit to form an undefined range. In addition, each separately disclosed point or single value itself can be combined with any other point or single value as a lower limit or upper limit or with other lower limits or upper limits to form an undefined range. The use of numerical ranges represented by endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.

[0038] The percentage contents involved in this application, unless otherwise specified, refer to mass percentage for solid-liquid mixing and solid-solid mixing, and refer to volume percentage for liquid-liquid mixing.

[0039] The percentage concentrations mentioned in this application, unless otherwise specified, refer to the final concentration, which refers to the percentage of the added component in the system after the addition of the component.

[0040] The temperature parameters in this application, unless otherwise specified, allow both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±2°C, ±1°C, ±0.5°C, ±0.4°C, ±0.3°C, ±0.2°C, and ±0.1°C are allowed. Normal temperature or room temperature in this application refers to no temperature control operation, generally 4°C~35°C, preferably 20±5°C.

[0041] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0042] A patent discloses a method for preventing the discoloration of PVDF-HFP slurry of lithium lanthanum zirconium tantalum oxide gel, which uses a washing method or a coating method to remove weak bases. The washing method is to remove trace amounts of weak bases from the oxide electrolyte filler by flushing with a large amount of organic solvent. This method has a long processing time, prolongs the overall production time, and it is difficult to completely remove the weak bases attached to the surface of the oxide electrolyte filler. The coating method is to use a coupling agent or a surfactant to coat an organic layer on the surface of the oxide electrolyte filler so that the weak base cannot contact the gel, thereby solving the problem of discoloration gel, but this process is more complicated and costly. There is also a patent that discloses a method for improving the discoloration and gelation of solid electrolytes and a method for preparing solid electrolytes, which uses a solution of an acidic substance (such as hydrochloric acid, sulfuric acid, nitric acid, oxalic acid, etc.) in the solid electrolyte to pretreat the oxide electrolyte filler, or directly add an acidic substance solution during the mixing process. This method will introduce water and corresponding acid salt impurities into the system, which will affect the ionic conductivity of the composite electrolyte.

[0043] In view of the fact that traditional methods such as acid washing and coating methods can only remove or isolate surface alkaline substances, there are problems such as incomplete removal of alkali or residual corresponding acid salt impurities affecting electrolyte performance. After a lot of research and development, the technicians of this application unexpectedly discovered that 3-triethoxysilyl ethyl propionate can be used to remove the residual alkali on the surface of the oxide electrolyte filler, enhance the interface compatibility between the oxide filler and the polymer, and thus provide better interface stability. That is, the present application provides a more efficient, simple and low-cost method for removing the residual alkali on the surface of the oxide electrolyte filler: by using 3-triethoxysilyl ethyl propionate to remove the residual alkali on the surface of the oxide electrolyte filler, the preparation process of the composite solid electrolyte can be optimized. Specifically, the ester group on the polymer additive will react with the residual alkali on the surface of the oxide electrolyte filler (LLZTO or LATP), namely LiOH (LiOH is generated by the reaction of Li2O and water in the air), to produce ethanol and triethoxysilyl lithium propionate. Ethanol evaporates when drying, and triethoxysilyl lithium propionate acts as a protective layer for the inorganic solid electrolyte. This avoids the influence of residual alkali on PVDF-HFP-based polymers, reduces the fluidity of the slurry, and prevents uneven film formation of the electrolyte membrane. The oxygen atoms on triethoxysilyl lithium propionate will coordinate with lithium ions, enhancing the boundary effect of the composite solid electrolyte. At the same time, the triethoxysilyl group and PVDF-HFP-based polymers have high solubility, which indirectly improves the compatibility between the oxide electrolyte filler and the PVDF-HFP matrix, ensuring the uniform distribution of the oxide electrolyte filler in the composite solid electrolyte.

[0044] In a first aspect of the present invention, a composite solid electrolyte membrane is provided, which comprises the following components:

[0045] Polyvinylidene fluoride-hexafluoropropylene, oxide powder, lithium salt and ethyl 3-triethoxysilyl propionate.

[0046] The present application uses 13-triethoxysilyl ethyl propionate with an ester group on the main chain to remove the residual alkali on the surface of the oxide electrolyte filler. This method is a novel residual alkali removal technical means that does not rely on traditional acid washing and coating treatment to ensure the stable performance of the oxide electrolyte filler. Using 3-triethoxysilyl ethyl propionate to remove the residual alkali on the surface of the oxide electrolyte filler enhances the interface compatibility between the oxide filler and the polymer, thereby providing better interface stability.

[0047] In some of the examples, the lithium salt includes one or more of lithium cyanide sulfide, LiN(CN)2, Li(CF3SO2)3C, LiC4F9SO3, LiN(SO2CF2CF3)2, LiB(C2O4)2, lithium bis(oxalate)borate, LiBF4, LiBF3(C2F5), lithium difluoro(oxalate)borate, lithium oxalatedifluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, LiAsF6, LiSbF6 and LiClO4.

[0048] In some of the examples, the oxide powder includes one or more of lithium lanthanum zirconium oxide powder, lithium aluminum titanium phosphate powder, lithium aluminum germanium phosphate powder and lithium lanthanum titanate powder.

[0049] In some examples, the mass ratio of ethyl 3-triethoxysilyl propionate to oxide powder is 1:(0.2-1.5). It can be understood that the mass ratio of ethyl 3-triethoxysilyl propionate to oxide powder includes but is not limited to 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5.

[0050] In some examples, the mass ratio of the oxide powder to polyvinylidene fluoride-hexafluoropropylene is (0.05-0.6): 1. It can be understood that the mass ratio of the oxide powder to polyvinylidene fluoride-hexafluoropropylene includes but is not limited to 0.05:1, 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1, 0.35:1, 0.4:1, 0.45:1, 0.5:1, 0.55:1, 0.6:1.

[0051] In some examples, the mass ratio of the polyvinylidene fluoride-hexafluoropropylene to the lithium salt is (1-20): 1. It can be understood that the mass ratio of the polyvinylidene fluoride-hexafluoropropylene to the lithium salt includes but is not limited to 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, 11: 1, 12: 1, 13: 1, 14: 1, 15: 1, 16: 1, 17: 1, 18: 1, 19: 1, 20: 1.

[0052] A second aspect of the present invention provides a method for preparing the composite solid electrolyte membrane as described above, comprising the following steps:

[0053] The oxide powder, ethyl 3-triethoxysilyl propionate and a solvent are mixed to prepare a mixed solution;

[0054] The polyvinylidene fluoride-hexafluoropropylene and lithium salt are added to the mixed solution, stirred, and dried to obtain the product.

[0055] In some of the examples, the step of preparing the mixed solution includes: directly mixing and stirring the oxide powder, ethyl 3-triethoxysilyl propionate and a solvent.

[0056] In some of the examples, the step of preparing the mixed solution includes: first mixing and stirring the ethyl 3-triethoxysilyl propionate and a solvent, and then adding the oxide powder.

[0057] In some of the examples, the conditions of the method for preparing the composite solid electrolyte membrane include: the solvent is N-methylpyrrolidone solvent.

[0058] In some of the examples, the conditions of the method for preparing the composite solid electrolyte membrane include: the drying temperature is 40° C. to 70° C. It can be understood that the drying temperature includes but is not limited to 40° C., 45° C., 50° C., 55° C., 60° C., 65° C., and 70° C.

[0059] In some of the examples, the conditions of the method for preparing the composite solid electrolyte membrane include: a drying time of 16 hours to 24 hours. It can be understood that the drying time includes but is not limited to 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, and 24 hours.

[0060] The preparation method of the composite solid electrolyte membrane of the present application does not require repeated washing and long-term treatment, the process is simple and environmentally friendly, reduces production time and energy consumption, and is suitable for industrial-scale application. Compared with traditional methods such as pickling and coating, the present application can achieve the effects of de-alkali and protection in a shorter time and is more suitable for large-scale production.

[0061] A third aspect of the present invention provides a solid-state battery comprising the composite solid-state electrolyte membrane as described above.

[0062] A fourth aspect of the present invention provides an electrical device comprising the solid-state battery as described above.

[0063] The following is further described in conjunction with specific embodiments. The raw materials involved in the following specific embodiments, unless otherwise specified, can all be commercially available; the instruments used, unless otherwise specified, can all be commercially available; the processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.

[0064] The 3-triethoxysilyl ethyl propionate (CAS: 6439-39-0) used in the examples and comparative examples can be purchased from the Kramar reagent platform, and the structure is as follows:

[0065] .

[0066] The following are specific embodiments.

[0067] Example 1

[0068] Step 1: Add 0.1 g of ethyl 3-triethoxysilyl propionate to 8 mL of N-methylpyrrolidone solvent (NMP) and stir magnetically for 2 h to ensure uniform mixing;

[0069] Step 2: Add 0.2 g of lithium lanthanum zirconium oxide powder to the above solution and disperse it by ultrasonic for 30 minutes to obtain a uniformly dispersed slurry;

[0070] Step 3: Add 0.5 g lithium salt LiTFSI and 1 g PVDF-HFP to the above slurry and stir magnetically for 12 h to ensure that the above materials form a uniform colloid.

[0071] Step 4: Use a scraper to apply the above glue solution on the surface of the glass plate, with a scraping thickness of 500 μm. After the scraping is completed, put the glass plate into a vacuum drying oven and dry it at 60°C for 20 hours to remove the NMP solvent, and then a composite solid electrolyte membrane can be obtained.

[0072] Example 2

[0073] Step 1: Add 0.2 g of lithium lanthanum zirconium oxide powder and 0.1 g of ethyl 3-triethoxysilyl propionate to 8 mL of N-methylpyrrolidone solvent, and stir magnetically for 8 h to ensure uniform mixing;

[0074] Step 2: Add 0.5 g lithium salt LiTFSI and 1 g PVDF-HFP to the above solution and stir magnetically for 12 h to ensure that the above materials form a uniform gel solution.

[0075] Step 3: Use a scraper to apply the above glue solution on the surface of the glass plate, with a scraping thickness of 500 μm. After the scraping is completed, put the glass plate into a vacuum drying oven and dry it at 60°C for 20 hours to remove the NMP solvent, and then a composite solid electrolyte membrane can be obtained.

[0076] Example 3

[0077] Step 1: Add 0.2 g of lithium lanthanum zirconium oxide powder and 0.04 g of ethyl 3-triethoxysilyl propionate to 8 mL of N-methylpyrrolidone solvent, and stir magnetically for 8 h to ensure uniform mixing;

[0078] Step 2: Add 0.5 g lithium salt LiTFSI and 1 g PVDF-HFP to the above solution and stir magnetically for 12 h to ensure that the above materials form a uniform gel solution.

[0079] Step 3: Use a scraper to apply the above glue solution on the surface of the glass plate, with a scraping thickness of 500 μm. After the scraping is completed, put the glass plate into a vacuum drying oven and dry it at 60°C for 20 hours to remove the NMP solvent, and then a composite solid electrolyte membrane can be obtained.

[0080] Example 4

[0081] Step 1: Add 0.2 g of lithium lanthanum zirconium oxide powder and 0.3 g of ethyl 3-triethoxysilyl propionate to 8 mL of N-methylpyrrolidone solvent and stir magnetically for 8 h to ensure uniform mixing;

[0082] Step 2: Add 0.5 g lithium salt LiTFSI and 1 g PVDF-HFP to the above solution and stir magnetically for 12 h to ensure that the above materials form a uniform gel solution.

[0083] Step 3: Use a scraper to apply the above glue solution on the surface of the glass plate, with a scraping thickness of 500 μm. After the scraping is completed, put the glass plate into a vacuum drying oven and dry it at 60°C for 20 hours to remove the NMP solvent, and then a composite solid electrolyte membrane can be obtained.

[0084] Comparative Example 1

[0085] Step 1: Add 0.2 g lithium lanthanum zirconium oxide powder, 0.5 g lithium salt LiTFSI and 1 g PVDF-HFP into 8 mL N-methylpyrrolidone solvent and mix them in one step, and stir them magnetically for 12 h to ensure uniform mixing;

[0086] Step 2: Use a scraper to apply the above glue solution on the surface of the glass plate, with a scraping thickness of 500 μm. After the scraping is completed, put the glass plate into a vacuum drying oven and dry it at 60° C. for 20 hours to remove the NMP solvent, and then a composite solid electrolyte membrane can be obtained.

[0087] Comparative Example 2

[0088] Step 1: Add 0.2 g lithium lanthanum zirconium oxide powder, 0.5 g ethyl 3-triethoxysilyl propionate, 0.45 g lithium salt LiTFSI and 0.9 g PVDF-HFP into 8 mL N-methylpyrrolidone solvent and mix in one step, and stir magnetically for 12 h to ensure uniform mixing;

[0089] Step 2: Use a scraper to apply the above glue solution on the surface of the glass plate, with a scraping thickness of 500 μm. After the scraping is completed, put the glass plate into a vacuum drying oven and dry it at 60° C. for 20 hours to remove the NMP solvent, and then a composite solid electrolyte membrane can be obtained.

[0090] By comparison, the one-step mixing method will lead to uneven distribution of materials, especially the uneven distribution of lithium lanthanum zirconium oxide fillers, which may cause membrane curling and low local ionic conductivity.

[0091] contrast Figure 1 and Figure 2 The prepared composite solid electrolyte membrane can be found that in Comparative Example 1, since no polymer additive is added for pretreatment, the slurry will change color and gel, and become jelly-like, so the coating uniformity is very poor, and the ion conductivity of the prepared product is low. Compared with the slurry without adding polymer additives, Examples 1 to 4 do not change color or gel.

[0092] At the same time, the composite solid electrolyte membranes prepared in Examples 1 to 5 and Comparative Example 1 were tested for performance such as thickness, impedance and ionic conductivity. The test results are shown in Tables 1 and Figure 3 shown.

[0093] Among them, the test conditions or test standards for each performance test item are:

[0094] Thickness: Select three different sites on a 2 cm2 composite electrolyte membrane and measure the thickness of each point with a screw micrometer. The average value is the thickness of the composite membrane.

[0095] Impedance: At room temperature, the electrolyte was assembled with two 16 mm stainless steel electrodes to form a SS | solid electrolyte | SS symmetric cell, which was connected to a Chenhua CHI760 electrochemical workstation. The ZPlot software was used to set the AC amplitude to 10 mV and the scanning frequency range to 10 6 ~10 -2 Hz, sweep from high frequency to low frequency to obtain the impedance spectrum, and finally complete the impedance fitting through Zview software to obtain the impedance R.

[0096] Ionic conductivity: The solid electrolyte impedance R is tested by the AC impedance method, and the conductivity σ can be calculated through the impedance R, the cross-sectional area S of the conductor, and the length L of the conductor as σ=L / RS.

[0097] Table 1

[0098]

[0099] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0100] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims, and the description may be used to interpret the content of the claims.

Claims

1. A composite solid electrolyte membrane, characterized in that: It includes the following components: Polyvinylidene fluoride-hexafluoropropylene, oxide powder, lithium salt and ethyl 3-triethoxysilyl propionate.

2. The composite solid electrolyte membrane according to claim 1, characterized in that: The lithium salt includes one or more of lithium cyanide, LiN(CN)2, Li(CF3SO2)3C, LiC4F9SO3, LiN(SO2CF2CF3)2, LiB(C2O4)2, lithium bis(oxalate)borate, LiBF4, LiBF3(C2F5), lithium difluoro(oxalate)borate, lithium oxalatedifluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, LiAsF6, LiSbF6 and LiClO4.

3. The composite solid electrolyte membrane according to claim 1, characterized in that: The oxide powder includes one or more of lithium lanthanum zirconium oxide powder, lithium aluminum titanium phosphate powder, lithium aluminum germanium phosphate powder and lithium lanthanum titanate powder.

4. The composite solid electrolyte membrane according to claim 1, characterized in that: The mass ratio of the 3-triethoxysilyl ethyl propionate to the oxide powder is 1:(0.2-1.5).

5. The composite solid electrolyte membrane according to claim 1, characterized in that: The mass ratio of the oxide powder to polyvinylidene fluoride-hexafluoropropylene is (0.05-0.6):

1.

6. The composite solid electrolyte membrane according to any one of claims 1 to 5, characterized in that: The mass ratio of the polyvinylidene fluoride-hexafluoropropylene and the lithium salt is (1-20):

1.

7. A method for preparing a composite solid electrolyte membrane according to any one of claims 1 to 6, characterized in that: The following steps are involved: The oxide powder, ethyl 3-triethoxysilyl propionate and a solvent are mixed to prepare a mixed solution; The polyvinylidene fluoride-hexafluoropropylene and lithium salt are added to the mixed solution, stirred, and dried to obtain the product.

8. The method for preparing a composite solid electrolyte membrane according to claim 7, characterized in that: The step of preparing the mixed solution comprises: directly mixing and stirring the oxide powder, ethyl 3-triethoxysilyl propionate and a solvent; and / or First, the ethyl 3-triethoxysilyl propionate and the solvent are mixed and stirred, and then the oxide powder is added.

9. A solid-state battery, characterized in that: A composite solid electrolyte membrane comprising any one of claims 1 to 6.

10. An electrical device, characterized in that: Including the solid-state battery as described in claim 9.